Effect of HYD Drugs on Hemolytic Anemia Induced by Phenylhydrazine Hydrochloride - O. A., Zayseva; Sh. M., Makhsumov; G. Yu., Djanaev; Sh. M., Mamadaliev (PT. Antis International Publisher, 2024)
In conclusion, the conducted experiments showed that the histostructure of the vital internal organs of rats in the control and experimental groups was almost the same. At the same time, drug-related histomorphological changes in their histostructure were not noted. It should be noted separately that the study of the histostructure of the liver and kidney from the parenchymatous organs of the animals that received the studied tincture showed that some morphological signs indicating their functional activity appeared. Therefore, long-term administration of the antianemic compound - DOY tincture to the body does not cause chronic poisoning in animals and any negative reactions in the histostructure of vital internal organs and biochemical analyzes of peripheral blood.